2010
DOI: 10.4161/auto.6.6.12574
|View full text |Cite
|
Sign up to set email alerts
|

The lipoatrophic caveolin-1 deficient mouse model reveals autophagy in mature adipocytes

Abstract: Adipose tissue lipoatrophy caused by caveolin gene deletion in mice is not linked to defective adipocyte differentiation. We show that adipose tissue development cannot be rescued by endothelial specific caveolin-1 re-expression, indicating primordial role of caveolin in mature adipocytes. Partial or total caveolin deficiency in adipocytes induced broad protein expression defects, including but not limited to previously described downregulation of insulin receptor. Global alterations in protein turnover, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 36 publications
1
29
1
Order By: Relevance
“…They might be linked to global reduction in adipocyte metabolic activity revealed here by gene expression defects in microarray analysis. Accordingly, autophagic degradation was recently reported in caveolin-deficient adipocytes (20), as well as compromised lipid droplet growth and maturation defects (21). …”
Section: Discussionmentioning
confidence: 99%
“…They might be linked to global reduction in adipocyte metabolic activity revealed here by gene expression defects in microarray analysis. Accordingly, autophagic degradation was recently reported in caveolin-deficient adipocytes (20), as well as compromised lipid droplet growth and maturation defects (21). …”
Section: Discussionmentioning
confidence: 99%
“…These results point to differential functions for cav-1 and cavin-1, and a potential role of cavin-1 in regulation of lipolysis, but fail to explain the lower LD size observed in the primary cav-1 deficient adipocytes. Finally, it was reported that cav-1 deficient adipocytes have increased autophagy but it remains to be experimentally demonstrated whether this mechanism contributes to decreased LD size by channeling LD lipids to lysosomal degradation [105]. …”
Section: Adipocyte-specific Ld Proteins With Direct Links To Insulmentioning
confidence: 99%
“…Since SREBP-1c is the predominant hepatic isoform among the SREBP family and CAV1 is regulated by SREBP-1 and is one of the LD proteins responsible for its stability, they were chosen to be the main focus of this study 11,44. In this context, this study aimed at uncovering the impact of miR-29a on SREBP-1c and its downstream target, CAV1, in order to better elucidate their roles in LD formation.…”
Section: Discussionmentioning
confidence: 99%
“…Many research groups have investigated the relation between CAV1 levels and LDs in different cell types, including adipocytes, fibroblasts and hepatocytes 11,2228. In a study of hepatocytes, NAFLD was shown to be associated with up-regulation of the hepatic CAV1 gene and protein expression as well as an increase in its localization on LDs 29,30.…”
Section: Introductionmentioning
confidence: 99%